The Impact of Quality Early Childhood Education Centers On Pre-schoolers’ Social Interaction - Suleiman Yusuf; Habibat Bolanle Abdulkareem; Balqis Olabisi Popoola (Indonesian Journal of Multidiciplinary Research, 2023)
The development of children can be harmed by low-quality early childhood education centers (ECEC), as these centers may hurt the children's overall well-being as well as their social, emotional, educational, physical, and behavioral results. It is challenging to pinpoint strategies. It could foster social interaction skills in young children due to a lack of agreement among educators regarding the strength of the relationship between relevant factors like teachers' qualifications, training, physical facilities, staff-child ratio, and the general standard of the ECE Center. In the Isin Local Government Area of Kwara State, the study looked at how preschoolers' social interactions were influenced by the quality of the ECE center. The research deliberately took into account schools having ECCDE centers. The observational evaluation scale on the impact of high-quality early childhood education centers on pre-schoolers' social interactions was one of two validated research instruments used to gather data. The other was the early childhood education center quality. The study recommends that schools provide extra hands-on materials, more playtime, and adequate space for play activities to foster children's social interaction through quality ECE Centers. The results showed that quality ECE Center had a positive influence on preschoolers' social interaction and overall development.